2013
DOI: 10.1152/jn.00676.2012
|View full text |Cite
|
Sign up to set email alerts
|

Modular control of varied locomotor tasks in children with incomplete spinal cord injuries

Abstract: Fox EJ, Tester NJ, Kautz SA, Howland DR, Clark DJ, Garvan C, Behrman AL. Modular control of varied locomotor tasks in children with incomplete spinal cord injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 76 publications
5
63
0
Order By: Relevance
“…Muscle synergies, also known as motor modules, can be defined as functional units of the nervous system that coordinate the coactivation of different groups of muscles. 16 Recent studies on the modular control of gait have shown that the activation of leg muscles during human locomotion can be reconstructed as a linear combination of four to five muscle synergies, each of which are activated at a different phase of the gait cycle [17][18][19] and underlying a specific biomechanical function. 15,20,21 Neurological impairments may alter the normal functioning of modular control and lead to gait disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle synergies, also known as motor modules, can be defined as functional units of the nervous system that coordinate the coactivation of different groups of muscles. 16 Recent studies on the modular control of gait have shown that the activation of leg muscles during human locomotion can be reconstructed as a linear combination of four to five muscle synergies, each of which are activated at a different phase of the gait cycle [17][18][19] and underlying a specific biomechanical function. 15,20,21 Neurological impairments may alter the normal functioning of modular control and lead to gait disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…As the number of synergies is an input of the NNMF, the algorithm was run using two, three, four and five synergies, for each subject. The variability accounted for (VAF) [15] was calculated as a metric of the similarity between original EMG and EMG reconstructed by multiplying matrix W by matrix H. The optimal number of synergies required to adequately reconstruct the EMG data was defined as the smallest number for which the overall VAF was ≥90% [6,15].…”
Section: Synergy Extractionmentioning
confidence: 99%
“…Several studies have shown that the EMG activity of trunk and leg muscles during human locomotion can be reconstructed as a linear combination of four to five basic modules, each one activated at a different phase of the gait cycle [5]. A module has been hypothesized to represent a functional unit of the nervous system that specifies functionally relevant patterns of muscle activation [6]. These modules, also called muscle synergies, quantitatively define the groups of muscles that are activated synchronously [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations